The efficacy of probiotics and/or n-3 long-chain polyunsaturated fatty acids intervention on maternal prenatal and postnatal depressive and anxiety symptoms among overweight and obese women - Hulkkonen Pauliina; Kataja Eeva-Leena; Vahlberg Tero; Koivuniemi Ella; Houttu Noora; Pellonperä Outi; Mokkala Kati; Karlsson Hasse; Laitinen Kirsi (Netherlands, 2022)
Maternal depression and anxiety may endanger well-being of both mother and child. We investigated the efficacy of probiotics and/or fish oil (FO) in modifying pre- and postnatal depressive and anxiety symptoms. Symptom trajectories were identified and the influence of lifestyle factors on symptoms was evaluated.\nOverweight women (n = 439) were randomized to intervention groups (probiotics+FO, probiotics+placebo, FO+placebo, placebo+placebo) from early pregnancy until six months postpartum, and assessed for depressive and anxiety symptoms with Edinburgh Postnatal Depression Scale (EPDS) and Anxiety subscale of Symptoms Checklist (SCL-90) at early and late pregnancy and three, six and 12 months postpartum. Latent growth mixture modeling was used to model the symptom courses. Dietary quality and physical activity were assessed with validated indices.\nSymptom scores were generally low. Statistically significant intervention effect was seen during pregnancy (p = 0.017): EPDS scores increased (by 1.11 points) in the FO+probiotics group and decreased (by 0.85 points) in the FO+placebo group. At 12 months postpartum, FO+placebo group had lower EPDS scores compared to probiotics+placebo group (p = 0.039). No differences in SCL scores were seen in response to the intervention. Irrespective of the intervention, three depressive and two anxiety symptoms trajectories were identified. Dietary quality correlated negatively with depressive symptoms in early pregnancy and six months postpartum and with anxiety symptoms in early pregnancy. Perinatal events including mother-reported colic were related to symptoms.\nSecondary outcomes of the primary trial.\nIntervention had a modest impact on depressive symptoms. Diet and obstetric events were associated with depressive and anxiety symptoms.\nBACKGROUND\nMETHODS\nRESULTS\nLIMITATIONS\nCONCLUSIONS